IMPLEMENTASI TEORI CHOMSKY DALAM BAHASA ALQURAN - Susiawati, Wati (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
This research aims to unravel Chomsky’s statment that generative transformation theory can be implemented in languages including Arabic. The main conclusions of this thesis was that generative transformation theory was carried out by Chomsky can be implemented into Alquran in all patterns. In Arabic grammar, however, especially in Alquran, these patterns were very diverse and varied. For example, there is a change in harakat, caused by the difference in position i'râb, al-ziyâdah which has lots of pattern or way, so did the placement pattern (al-ihlâl) and pattern i'âdat al-tartîb particularly at taqdîm wa ta'khîr and hadhf. However, the accuracy of Alquran sellection and the process of arrangement were truly remarkable, not only because of its i'jâz, but this is reflected in the results of the study and the findings of the theory of generative transformation implemented in Arabic Alquran.